Acute activation of SERCA with CDN1163 attenuates IgE‐mediated mast cell activation through selective impairment of ROS and p38 signaling. Issue 2 (9th January 2023) - Hunter, Katie D.; Crozier, Robert W. E.; Braun, Jessica L.; Fajardo, Val A.; MacNeil, Adam J.
Abstract: Mast cells are granulocytic immune sentinels present in vascularized tissues that drive chronic inflammatory mechanisms characteristic of allergic pathologies. IgE‐mediated mast cell activation leads to a rapid mobilization of Ca 2+ from intracellular stores, which is essential for the release of preformed mediators via degranulation and de novo synthesized proinflammatory cytokines and chemokines. Given its potent signaling capacity, the dynamics of Ca 2+ localization are highly regulated by various pumps and channels controlling cytosolic Ca 2+ concentrations. Among these is sarco/endoplasmic reticulum Ca 2+ ‐ATPase (SERCA), which functions to maintain low cytosolic Ca 2+ concentrations by actively transporting cytosolic Ca 2+ ions into the endoplasmic reticulum. In this study, we characterized the role of SERCA in allergen‐activated mast cells using IgE‐sensitized bone marrow‐derived mast cells (BMMCs) treated with the SERCA activating compound, CDN1163, and simultaneously stimulated with allergen through FcεRI under stem cell factor (SCF) potentiation. Acute treatment with CDN1163 was found to attenuate early phase mast cell degranulation along with reactive oxygen species (ROS) production. Additionally, treatment with CDN1163 significantly reduced secretion of IL‐6, IL‐13, and CCL3, suggesting a role for SERCA in the late phase mast cell response. The protective effects of SERCA activation via CDN1163 treatment on the early and late phase mast cell response may be driven by the selective suppression of p38 MAPK signaling. Together, these findings implicate SERCA as an important regulator of the mast cell response to allergen and suggest SERCA activity may offer therapeutic potential targeting allergic pathologies, warranting further investigation.